Indoor allergen exposure and asthma outcomes. Issue 6 (December 2016) - Sheehan, William J.; Phipatanakul, Wanda
Abstract : Purpose of review: The aim of the present review is to discuss updates on research regarding the relationship between indoor allergen exposure and childhood asthma with a focus on clinical effects, locations of exposure, and novel treatments. Recent findings: Recent data continue to demonstrate that early life sensitization to indoor allergens is a predictor of asthma development later in life. Furthermore, avoidance of exposure to these allergens continues to be important especially given that the vast majority of children with asthma are sensitized to at least one indoor allergen. New research suggests that mouse allergen, more so than cockroach allergen, may be the most relevant urban allergen. Recent evidence reminds us that children are exposed to clinically important levels of indoor allergens in locations away from their home, such as schools and daycare centers. Exposure to increased levels of indoor mold in childhood has been associated with asthma development and exacerbation of current asthma; however, emerging evidence suggests that early exposure to higher fungal diversity may actually be protective for asthma development. Novel treatments have been developed that target TH2 pathways thus decreasing asthmatic responses to allergens. These therapies show promise for the treatment of severe allergic asthma refractory to avoidance strategies and standard therapies. Summary: Understanding the relationship between indoor allergens and asthma outcomes is a constantly evolving study of timing, location, and amount of exposure.